Corporate social responsibility (CSR) and development: the case of gender equality in Latin America - Torres Retamal, Luis Dario (2017)
The 2030 global development agenda represents a renewed commitment to gender equality and an explicit call for business contribution. Even though during the last 15 years the gender gap has narrowed, women continue to lag behind men in the economic opportunities available to them. Feminist economists have largely acknowledged that many gender inequalities happen in organisations and, therefore, business organisations have much to contribute. In this respect, one of the most significant shifts of the post-2015 agenda has been the explicit call for a more proactive role of the private sector. Responsible business practices or Corporate Social Responsibility (CSR) represent an opportunity for the effective incorporation of gender issues into the business strategy. However, the actual integration of gender issues in the CSR agenda has been limited, CSR has been frequently studied at one level at a time (macro, organisational or individual), research has been primarily carried out in developed regions such as Europe and North America, and the practice of CSR has been characterised by a more external focus on philanthropic environmental and community activities.